Analysis of urban network operation in presence of renewable sources for decarbonization of energy system - Balaban, Georgiana; Dumbrava, Virgil; Lazaroiu, Alexandra Catalina; Kalogirou, Soteris A. (My University, 2024)
In order to decarbonize the energy system, it is necessary to change all aspects of the production, transport and consumption of electricity chain. The European Union (EU) aims to become the first climate-neutral continent by 2050. To deliver on this ambition, decarbonising the energy sector is crucial because the production and use of energy accounts for more than 75 % of the EU's greenhouse gas emissions (EEA, 2021). The connection of renewable sources near the places of consumption can lead to flexibility in changing the operating diagram, the operator having the possibility to keep certain distribution cables disconnected, which diminishes the reactive power circulating through the distribution network. The article analyzed two types of distribution areas that show that in the area where consumption is high, it is easier to implement measures to transform the area into positive energy. The concept The concept of Ecs (“energy communities”) provides a great boost for overcoming resistance to infrastructure development, increasing acceptance and penetration of distributed energy resources (DERs), encouraging private investments, and establishing public-private partnerships.
Keywords: Decarbonization; Distributed energy resources; Continuity of supply